Unifying the Orthopaedic Surgery Residency Application Process Under a Single Accreditation System: A Primer. Issue 7 (1st April 2020) - Aiyer, Amiethab; Sankar, Vignesh; Summers, Spencer; Rush, Augustus; Kaplan, Jonathan R. M.; Varacallo, Matthew; Marsh, J. Lawrence; Levine, William N.
Abstract : In 2020, the Accreditation Council for Graduate Medical Education and the American Osteopathic Association will merge creating a single accreditation system for graduate medical education in the United States under the National Residency Match Program. The goal of this merger is to ensure nationwide consistency in purpose and practice of medical care in the United States, specifically in the context of residency education and training for the next generation of physicians. The proposed impact is still speculative since we do not know what lasting effects, if any, this merger will have on subspecialties such as orthopaedic surgery. There are many considerations that medical school advisors need to take into account when guiding their students applying to residency after the match merge. The newly unified accreditation system will pose additional competition, considering that there will be more applicants than spots available in competitive specialties, including orthopaedic surgery. These are important caveats to keep in mind as the residency application process is evolving actively. It is the authors' hope that concepts discussed in this article stimulate further discussion, catalyze research, and optimize the ability for students to succeed in the match process.